B)
here,
A to B = 62
C To B = 11
A to C = ?
now,
so, 62 - 11 = 51
therefore a to C Is 51 cm
plz mark me brainliest ok
plz follow me
A)
Here,
A to B = 13
A to C = 26
total = ?
now,
A to B + A to C
13 + 26 = 39
Therefore,
total number is 39
Answer:
B (-2 , -11)
Step-by-step explanation:
hello : the system is :
y = 4x - 3
y= -x - 13
put x = -2
y = 4(-2) - 3=- 11
y= -(-2) - 13 = -11
The answer is A because 2time 2 is 4-2 =2 and then 120times 2 =240
(2p + q)(-3q - 5)
(2p + q)(-5 -3q)
-10p -6pq -5q -3q^2
-3q^2 -5q -6pq -10p